Effects Of Growth Parameters On The Synthesis And Characteristics Of Apcvd Grown Graphene For Photosensing Applications - Abdalrheem, Raed Abdelmajeed Mohammad (2020)
The graphene has gained a tremendous interest of researchers in recent years due to its amazing properties. In the present work, graphene films have been synthesized by the CVD technique at atmospheric pressure. The effects of growth conditions on the quality, structural and optical properties were investigated. The study was carried out using appropriate characterization tools including Raman spectroscopy, UV-Vis spectrometer, FESEM, AFM, and XPS. The study revealed that the Ni substrate promotes the formation of a multi-layered graphene whereas the Cu has the advantage of producing mono to few-layered graphene films. Studying the effect of the N2 flow rate on graphene growth showed that the graphene layers number, defects level, and defect density decreased by the increment of the N2 flow rate. At N2 flow rates of 1600 sccm, high-quality monolayer graphene with relatively low defects level (ID/IG ~08), appropriate FWHM2D ~ 29 cm-1 and high 2D to G intensities ratio (I2D/IG~ 2.4) were obtained. Besides, a comparative study was conducted on graphene transfer methods including electrochemical delamination (ECD) and chemical metal etching (CME). The graphene film which was transferred by ECD has the lowest defects/disorder level ID/IG ~ 0.05 that led to better graphene quality. Furthermore, graphene was grown by atmospheric pressure chemical vapor deposition (APCVD) method using 1-butanol as a new liquid precursor for carbon. A new modification on the growth procedure was implemented.